Paraconductivity analysis for Ni-doped BSCCO - Dihor, Ion (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2005)
The paraconductivity effect of Ni-doped 2223 BSCCO ceramic samples was studied using data obtained from resistive measurements. The temperature ranges of 2D and 3D regimes of fluctuation conductivity as well as the crossover between different temperature regimes were determined in terms of the Lawrence and Doniach theory of fluctuations.